Bowie : an illustrated life - Hesse, María; Ruiz, Fran (University of Texas Press, 2019)
"David Bowie was a master of artifice and reinvention. In that same spirit, illustrator Marâia Hesse and writer Fran Ruiz have created a vivid retelling of the life of David Robert Jones, from his working-class childhood to glam rock success to superstardom, concluding with the final recording sessions after his cancer diagnosis. Narrated from the rock star's point of view, Bowie colorfully renders both the personal and the professional turning points in a life marked by evolution and innovation. We see Bowie facing the sorrow of his brother's mental illness, kicking a cocaine habit while other musicians succumbed to deadly overdoses, contending with a tumultuous love life, and radiating joy as a father. Along the way, he describes how he shattered the boundaries of song and society with a counterculture cast that included Iggy Pop, Brian Eno, and Freddie Mercury--as well as his own creations, Ziggy Stardust and the Thin White Duke."--Publisher's description.